Semantic processing in children with cochlear implants: Evidence from event-related potentials. Issue 6 (3rd July 2019) - Bell, Nicola; Angwin, Anthony J.; Arnott, Wendy L.; Wilson, Wayne J.
ABSTRACT: Introduction : Existing research has shown that children with significant hearing loss who use cochlear implants (CIs) perform worse than their hearing peers on behavioral measures of spoken language. The present study sought to examine how children with CIs process lexical–semantic incongruence, as indexed by electrophysiological evidence of the N400 effect. Method : Twelve children with CIs, aged between 6 and 9 years, participated in a spoken word–picture matching task while event-related potentials (ERPs) were recorded. To determine whether the N400 effect elicited in this group deviated from normal, independent samples t tests and analysis of variance (ANOVA) analyses were used to compare the results of children with CIs against those of a similarly aged typically hearing (TH) group ( n  = 30). Correlational analyses were also conducted within each group to gauge the degree to which the N400 effect related to behavioral measures of spoken language. Results : An N400 effect was elicited in both groups of CI and TH children. The amplitude and latency of the N400 effect did not differ significantly between groups. Despite the similarity in ERP responses, children with CIs scored significantly lower on behavioral measures of spoken word- and sentence-level comprehension. No significant correlations between ERP and behavioral measures were found, although there was a trending relationship between sentence-level spoken language comprehension and the TH group's N400 effect mean amplitude ( p  = .060). Conclusions : The results suggest that, at a neural level, children with CIs can process lexical–semantic incongruence, and that other underlying processes not measured by the N400 effect contribute to this population's spoken language difficulties.